Animal parasites in man - Swellengrebel, N. H. b. 1885. 4 0 (Nicolas Hendrik),16; Sternman, Max M.; 5 (Princeton, N.J. : Van Nostrand, 1961)
Stresses biological and ecological factors and covers diagnosis and treatment.
Based on a standard Dutch work.
Includes bibliography.
Keywords: 2 -- 0; 6; Medical parasitology.;Bacteriology.;Parasites.; 20; 2